Diabetes patients' perspectives on the patients' rights: evidence from east of Iran. Issue 4 (29th August 2019) - Sharifzadeh, Gholam Reza; Ghoddoosi-Nejad, DJavad; Behdani, Susan; Haghgoshayie, Elaheh; Siraneh, Yibeltal; Hasanpoor, Edris
Abstract : Purpose: The Iranian patients' rights charter defines patient rights as a reflection of fundamental human rights in the field of medicine and incorporates all elements of patient rights accepted in international texts. The purpose of this paper is to study the way in which diabetes patients' rights are being exercised in everyday hospital practice in Birjand, Iran. Design/methodology/approach: A cross-sectional study design was used in 2014. The sample size was estimated 150 patients, out of which 108 diabetes patients completed questionnaire. The questionnaire of diabetes patients' perspectives on the patients' rights was used to collect data. The questionnaire consists of 22 questions. Data entry and analysis were carried out using SPSS software (version 22). Descriptive and inferential statistics were calculated with all survey items and total scores, as well as demographic data. Findings: The response rate was 72 percent. Overall, the mean score percentage of diabetes patients' perspectives on the patients' rights was 74.04± 8.4. Furthermore, statistical significant differences were found among diabetes patients in relation to patients' perspectives on the patients' rights according to highest level of education ( F =16.52, p =0.002), their habitat( t =3.49, p =0.001), age groups ( F =18.70, p =0.0001) and the duration of the disease ( F =5.16, p =0.007). The results showed that no statistically significant differences were observed among diabetes patients in relation to diabetes patients' perspectives on the patients' rights according to their gender ( F =1.57, p =0.12) and marital status ( F =1.56, p =0.09). Originality/value: Clinicians can provide care based on patients' rights, and their knowledge of patients' rights needs to be evaluated. Educational courses, leaflets, booklets and posters can be helpful in this regard. In addition, professional organizations and the Ministry of Health need to be more sensitive to this issue.